Kyai's Collective Collegial Leadership Model in Education Management - Ahmad, Ahmad Zulfa; Nursyam, Nursyam; Khuamidi, Anis (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Leadership in Islamic education is facing growing challenges that require a shift from single-authority systems toward more collaborative and participatory governance. This study aims to analyze how the collective-collegial leadership model of the kyai operates in managing Islamic educational institutions. Using a qualitative case study design, data were collected through in-depth interviews, field observations, and document analysis involving kyais, administrators, and committee members. The findings reveal three major themes: distributed authority that balances moral legitimacy and administrative efficiency; collaborative governance that ensures transparency, shared responsibility, and policy sustainability; and collective leadership that institutionalizes a unified organizational vision through formal documentation. The study’s novelty lies in integrating Islamic values of (deliberation), ukhuwah (brotherhood), and amanah (trust) into a structured model of participatory leadership. The results imply that leadership development in Islamic education should emphasize ethical collaboration, institutional documentation, and inclusive decision-making to achieve long-term organizational resilience.